2010
DOI: 10.1148/radiol.10091341
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma: A Method for Predicting Response to Antiangiogenic Chemotherapy by Using MR Perfusion Imaging—Pilot Study

Abstract: Purpose:To derive a magnetic resonance (MR)-based imaging metric that refl ects local perfusion changes resulting from the administration of angiogenic-inhibiting chemotherapy in patients with recurrent glioblastoma multiforme (GBM). Materials and Methods:In this retrospective Institutional Review Board-approved HIPAA-compliant study, 16 patients (12 men, four women; mean age, 51.8 years 6 15.1 [standard deviation]) with recurrent GBM received bevacizumab every 3 weeks (15 mg per kilogram of body weight) as pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 14 publications
4
47
2
1
Order By: Relevance
“…Four studies of recurrent HGGs have reported early pharmacodynamic reductions in K trans following bevacizumab with or without cytotoxic therapy between 4 days and 6 weeks after initiation of therapy, akin to mRCC and HCC data. However, unlike the results from mRCC and HCC studies, reductions in K trans did not show significant relationships with PFS or OS in HGG (44,45,47,48). These data differ from a similar sized study of 28 glioblastoma multiforme patients with recurrence treated with cediranib, where early reduction in K trans was significantly related to OS (49).…”
Section: High-grade Gliomacontrasting
confidence: 60%
See 1 more Smart Citation
“…Four studies of recurrent HGGs have reported early pharmacodynamic reductions in K trans following bevacizumab with or without cytotoxic therapy between 4 days and 6 weeks after initiation of therapy, akin to mRCC and HCC data. However, unlike the results from mRCC and HCC studies, reductions in K trans did not show significant relationships with PFS or OS in HGG (44,45,47,48). These data differ from a similar sized study of 28 glioblastoma multiforme patients with recurrence treated with cediranib, where early reduction in K trans was significantly related to OS (49).…”
Section: High-grade Gliomacontrasting
confidence: 60%
“…This parameter has also distinguished progressors from nonprogressors in patients receiving bevacizumab and cytotoxic therapy (56). Similarly, studies report that the amount of tumor with high BV (48) or low/skewed apparent diffusion coefficient (ADC) values (57)(58)(59) show a relationship to tumor PFS and OS that is obscured when average values of BV and ADC are used. However, these approaches rely on a priori assumptions to define the subregion of interest, and further work is required to define objective, data-driven tumor regions (60,61) that relate to response, relapse, and clinical outcome.…”
Section: Role Of Measuring Tumor Heterogeneitymentioning
confidence: 99%
“…The estimated relative cerebral blood volume measured by perfusion MRI is a semiquantitative parameter that correlates with the number of capillaries (22) and glioma grading (23). MRI perfusion showed correlations with PFS during antiangiogenic treatment (24) and can differentiate between recurrent tumor and pseudoprogression (25). Chen et al (18) evaluated antiangiogenic treatment response using 39-deoxy-39-18 F-fluorothymidine.…”
Section: Discussionmentioning
confidence: 99%
“…This quantitation process was performed automatically and without manual intervention by using in-house software written in Matlab (Matlab 2009a; Mathworks, Natick, Mass), based on the bookend method outlined above and previously applied in clinical studies of cancer (18,19), multiple sclerosis (20), and acute stroke (21). In large clinical studies this automated perfusion quantitation technique has been found to be robust, repeatable, and reliable (15).…”
Section: Pet Protocolmentioning
confidence: 99%